Speech by Prof. Daniel Mugendi Njiru, Vice-Chancellor, University of Embu During the 3rd University of Embu Careers’ Day Held on Saturday, 9th February, 2019 - Mugendi, Daniel N. (University of Embu, 2019)
The event’s main aim is to equip high school students in the region with the necessary information to help them make informed career choices in life.